(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Pediatric infective endocarditis (IE) is an uncommon but serious infection of the endocardial surface of the heart, often resulting in significant morbidity and mortality among children with underlying cardiac abnormalities. Despite medical advances, diagnostic delays and changing microbial patterns continue to pose challenges in developing countries. Objective: The objective of the research was to determine the estimation of the clinical, demographic, and microbiological patterns of pediatric infective endocarditis among patients who presented themselves to Department of Pediatrics Cardiology, MTI, Peshawar Institute of Cardiology, Peshawar. Methods: The study was a cross-sectional study that was carried out at Department of Pediatrics Cardiology, MTI, Peshawar Institute of Cardiology, Peshawar in the period of From 1st January, 2024 to 31st December, 2024. It included 68 reduced pediatric cases of infective endocarditis meeting the modified Duke criteria, ranging from 1 month to 16 years old. Descriptive statistics helped in the collection and analysis of the demographic data, clinical presentation, echocardiography data, and blood culture. Results: The average age of the patients was 8.77 ± 4.21 years, and the ratio of males to females was 1.3:1. Fever (91.2%) and cardiac murmur (72.1%) were the most frequent clinical manifestations. Echocardiography showed the presence of the mitral valve in 41.2 percent of cases. Staphylococcus aureus (39.7%) and Streptococcus viridans (30.9%) were the most frequent pathogens in this case. Blood cultures were negative in 10.2% of the cases. The mean length of stay of the hospital was 14.6 ± 5.3 days, and the In-hospital mortality rate was 5.9 percent. Conclusion: Pediatric infective endocarditis is one of the severe health conditions in the tertiary care hospital. Early diagnosis and proper antibiotic management, echocardiographic screening, and enhanced measures of infection control are important in enhancing the clinical outcomes and mortality in the affected children.